Advocacy journalism and the organisational factors that support it. A study of Personal Finance in the context of coverage of the retirement annuity reform issue in South Africa - Pandy, Thoraya (My University, 2009)
Abstract This research report will evaluate Personal Finance as a news organisation. This will be done in order to uncover the organisational factors which support the emergence of a certain style of reporting by the publication, namely that of advocacy journalism. Traditional structural factors such as hierarchies of power, management structures and reporting routines and practices will be examined. However, other factors inherent to the news organisation, such as organisational values and the levels of professionalism and ethics will also be evaluated, as these factors can be seen as important to an organisation, influencing the style of reporting which emerges. The report will also present the findings of a case study which seeks to illustrate how the publication displayed an advocacy journalism style of reporting in its coverage of a specific issue. It will concentrate on the publication’s coverage of faults and reform in the life assurance industry in South Africa, which spanned a period of more than ten years. Based on this case study, the report will then uncover how various aspects of the organisational structure of Personal Finance resulted in the issue being covered as a story as well as the style of reporting on this issue. The social organisational theory of news production will be used as a theoretical focus. Theories of news production and the agenda-setting theory of mass media will also be used. Research will be qualitative in nature and include interviews and content analysis of relevant articles.